Examining Students’ Procedural Skills through the Construction of an Electroscope in Electrostatics Instruction - Suminar, Iin; Noviana, Mochammad Irfan; Saputra, M. Reza Dwi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
The aim of this study is to examine students’ procedural skills engagements through a low-tech, hands-on physics experiments involving the construction of an electroscope during electrostatics instruction. A total of 27 students, organized into eight collaborative groups, participated in the activity, which emphasized student autonomy in selecting materials, designing components, and performing technical adjustments such as stripping wire insulation. Adopting a descriptive qualitative approach, data were collected through classroom observations and assessed using a rubric that measured four key dimensions:. material preparation, following the steps of the experiment, problem-solving and troubleshooting, and observational skills and interpretation. The results indicate that the majority of student groups demonstrated proficient to exemplary performance across most dimensions, particularly in material handling and interpreting experimental outcomes. These findings underscore the educational value of analog experimentation in fostering students’ procedural competencies, supporting hands-on engagement, and reinforcing foundational scientific practices in a digitally evolving classroom environment.